2022
DOI: 10.3390/horticulturae8010070
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Phenolic Compounds of Fruit Peels of Different Ecotype Bananas Derived from Domestic and Imported Cultivars with Different Maturity

Abstract: Banana is one of the most produced and consumed fruits in the world and its fruit peel accounts for about 40% of the total fresh quantity of ripe fruit, which is usually regarded as waste and poses serious environmental hazards. However, it is a promising source of natural bioactive compounds including phenolic compounds. Determination of the phenolic compounds in fruit peel from different cultivars and subgroups over a range of maturities provides convincing information for making full use of them. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Phenolic acid results indicate that QA and CA are the predominant phenolic compounds present in the pericarp of banana fruit, and GA, CC, FA, and PA were found in minimal amounts. This is in accordance with the study of Zhang et al [81]. Several studies indicate that derivatives of QA, such as CA and GA, possess beneficial health effects, including antioxidant, antimicrobial, anti-inflammatory, and neuroprotective properties.…”
Section: Changes In Phenolic Acidssupporting
confidence: 92%
“…Phenolic acid results indicate that QA and CA are the predominant phenolic compounds present in the pericarp of banana fruit, and GA, CC, FA, and PA were found in minimal amounts. This is in accordance with the study of Zhang et al [81]. Several studies indicate that derivatives of QA, such as CA and GA, possess beneficial health effects, including antioxidant, antimicrobial, anti-inflammatory, and neuroprotective properties.…”
Section: Changes In Phenolic Acidssupporting
confidence: 92%
“…These events may lead to increased oxidative stress and cause many metabolic changes associated with ripening and maturation. Zhang et al (2022) reported that green banana peel can be used as a high-quality raw material for extracting phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked ROS to a variety of chronic diseases, including neurodegeneration, cancer, diabetes, and inflammation [84]. Rutin and myricetin are the most abundant phenolic compounds in plantain and dessert banana peel flavonol profiles [85]. According to Phacharapiyangkul et al [86], ferulic acid, which is abundant in sucrier banana peel, may act as an anti-melanogenesis factor by regulating vascular endothelial growth factor expression, initiating nitric oxide synthase, and acting as a tumor suppressor gene.…”
Section: Health Benefits Of Banana By-productsmentioning
confidence: 99%